Dossier I: La huella de Jack "el destripador": dos casos de desmembramiento criminal necromaníaco en España - Mata Tutor, Pilar (Quadernos de criminología, 2021)
A descriptive analysis of 35 Spanish forensic cases from 1990 to 2020 was conducted. Two of them had a "modus operandi" like Jack "the Ripper". It was established that the necromaniac subtype has an incidence of 5.71 % regarding dismemberment cases, and 0.016 % regarding homicide cases, confirming that it is a unusual subtype.